1998
DOI: 10.1038/bjc.1998.272
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of 3-week tamoxifen treatment on oestrogen receptor levels in primary breast tumours: a flow cytometric study

Abstract: Summary The effect of 3-week, preoperative tamoxifen treatment on oestrogen receptor (ER) levels, expressed by primary breast tumours, was examined. Patients (age-matched) with breast cancer, confirmed by fine-needle aspiration, were either treated with 20 mg ml-' oral tamoxifen per day or received no medication in the 3-week interval between assessment and surgery. Quantification of ER using flow cytometry was performed on the surgically removed tumour samples from tamoxifen-treated (n = 40) and control (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…We found that both low‐ and high‐dose tamoxifen reduced the expression of mammary epithelial ER by 5% to 8% in absolute percent difference, respectively, in premenopausal women. Our findings are in line with most previous studies investigating the effects of short‐term tamoxifen in breast tumours of predominantly premenopausal women showing that tamoxifen for up to 6 weeks at various doses significantly reduces the expression of ER in tumours or adjacent tissues 12,14,30‐34 . Our study is the first showing longer‐term effects up to 6 months of tamoxifen in the normal breast epithelium.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that both low‐ and high‐dose tamoxifen reduced the expression of mammary epithelial ER by 5% to 8% in absolute percent difference, respectively, in premenopausal women. Our findings are in line with most previous studies investigating the effects of short‐term tamoxifen in breast tumours of predominantly premenopausal women showing that tamoxifen for up to 6 weeks at various doses significantly reduces the expression of ER in tumours or adjacent tissues 12,14,30‐34 . Our study is the first showing longer‐term effects up to 6 months of tamoxifen in the normal breast epithelium.…”
Section: Discussionsupporting
confidence: 92%
“…showing that tamoxifen for up to 6 weeks at various doses significantly reduces the expression of ER in tumours or adjacent tissues. 12,14,[30][31][32][33][34] Our study is the first showing longer-term effects up to 6 months of tamoxifen in the normal breast epithelium. In contrast to the association between reduced proliferation and epithelial area, we did not find any association between lower levels of epithelial ER and epithelial area change in women treated with tamoxifen.…”
Section: Discussionmentioning
confidence: 57%
“…The cell suspension was divided into two equal portions, one for assessment of cellular DNA content and cell cycle phase fractions and one for the apoptosis assay. We have previously used cytokeratin gating in disaggregated breast cancers after saponin treatment to render cells permeable to antibodies (Brotherick et al, 1998). However, cytokeratin gating and assay of apoptosis in the same sample by the method of the present study is not possible.…”
Section: Preparation Of Primary Colorectal Tumour Tissuementioning
confidence: 87%
“…2A). A similar technique of flow cytometric detection of cytokeratin-positive cancer cells was evaluated in breast cancer cells [11,12], in small cell carcinoma [13] and for detection of lymph node metastasis in non-small cell lung carcinoma [14]. The expression of Pgp, MRP1 or LRP was quantified by the percentage of positive cells according to isotype-matched control staining, and the results were scored as the frequency of positive carcinoma cells [15].…”
Section: Flow Cytometric Analysismentioning
confidence: 99%